GALLSTONES IN PEDIATRIC HEMATOPOIETIC CELL TRANSPLANT SURVIVORS WITH UP TO 40 YEARS OF FOLLOW-UP - Hoffmeister, Paul A. (J Pediatr Hematol Oncol, 2014)
PURPOSE: To determine risk factors for the development of gallstones and the prevalence of related cholecystectomy in children following hematopoietic cell transplantation (HCT). PATIENTS AND METHODS: A retrospective chart review of 1,343 patients aged <18 years old who survived at least one year after HCT from 1969–2011 was performed. Multivariate Cox regression models were used to estimate the hazard ratio (HR) of risk factors associated with gallstones. RESULTS: Gallstones developed in 91 patients, a median of 3.5 (0.1 to 30.9) years after HCT at 16.3 (0.8 to 44.2) years of age, with a 40-year cumulative incidence of 11%. At initial diagnosis, 61 (67%) patients were symptomatic and 30 (23%) had incidental gallstones. Risk factors associated with gallstones included autologous transplant (HR = 2.7, p = .02), unrelated donor (HR=2.0, p=.05), grade 3–4 acute graft-versus-host disease (GVHD) (HR = 2.2, p = .03), chronic GVHD (HR = 2.0, p = .05), second transplant (HR = 2.3, p = .03), diabetes (HR = 2.2, p = .05) and estrogen therapy (HR = 1.8, p=.03). Fifty-six patients underwent cholecystectomy. The prevalence of cholecystectomy among 853 surviving patients was 5.2%. CONCLUSIONS: Childhood HCT patients have an increased risk of developing gallstones.